The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.21273/hortsci.39.2.256
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Late-season 15N-labeled Fertilizer Applied to Pecan

Abstract: The recovery of late-season (September) 15N-labeled fertilizer (N at 55 kg·ha-1) was followed in mature pecan trees [Carya illinoinensis (Wangehn.) K. Koch] and soil (0-270 cm) from 1996 (application year) through 2001 (end of study). Recovery of late-season applied 15N was compared to the recovery of six 15N applications (March through June, N at 221 kg·ha-1) of a previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Yield was unaffected by treatment during the study (Table 6). Nitrogen depletion by large crops has been proposed to contribute to pecan alternate bearing (Goff et al, 2001;Kraimer et al, 2004;Wood, 2001). In this study, nitrogen was supplied throughout the growing season in excess, but alternate bearing was apparent.…”
Section: Resultsmentioning
confidence: 99%
“…Yield was unaffected by treatment during the study (Table 6). Nitrogen depletion by large crops has been proposed to contribute to pecan alternate bearing (Goff et al, 2001;Kraimer et al, 2004;Wood, 2001). In this study, nitrogen was supplied throughout the growing season in excess, but alternate bearing was apparent.…”
Section: Resultsmentioning
confidence: 99%
“…Scientists have also speculated that the amount of stored N might be closely associated with alternate bearing (Goff et al, 2001;Kraimer et al, 2004;Wood, 2001a), although studies on pecan have shown little response or a negative response to fall applied N (Acuña- Maldonado et al, 2003;Smith et al, 2004). Because K plays a critical role in carbohydrate and N transport, we also monitored root concentrations to determine if K was associated with crop thinning.…”
Section: Discussionmentioning
confidence: 99%
“…Acuña-Maldonado et al (2003) reported the greatest N absorption between budbreak and the end of shoot expansion, with little absorption between the end of leaf expansion and leaf fall. Kraimer et al (2004) later reported that N applied during the kernel filling stage was strongly absorbed. The newly absorbed N replenished endogenous N reserves and might moderate pecan alternate bearing.…”
mentioning
confidence: 99%
“…For example, pecan, a perennial tree crop grown in southern New Mexico, is commonly fertilized with 250 lbs N per acre (281 kg/ha) per year (Herrera, 2003) and irrigated with 59 in. (150 cm) of water annually (Kraimer et al, 2004). The non‐N‐limiting pecan irrigation water would contain an average of 19 mg/L N. In this case, the effluent has a relatively low TKN concentration (three‐year running average of 11.3 mg/L).…”
Section: Las Cruces Project Provides Irrigation Scheduling Prototypementioning
confidence: 99%